The Ups and Downs of Parenting Young Children With Type 1 Diabetes: A Crowdsourcing Study. (22nd March 2017) - Pierce, Jessica S.; Aroian, Karen; Caldwell, Cindy; Ross, Judith L.; Lee, Joyce M.; Schifano, Elizabeth; Novotny, Rebecca; Tamayo, Anthony; Wysocki, Tim
Abstract: Objectives: Parenting young children with type 1 diabetes (YC-T1D) entails pervasive challenges; parental coping may influence child and parent outcomes. This study used a qualitative descriptive design to describe these challenges comprehensively to inform the user-centered design of an Internet coping resource for parents. Methods: A "Parent Crowd" of 153 parents of children with T1D onset at ≤ 5 years old submitted textual responses online to open-ended questions about parenting YC-T1D. Systematic coding organized responses into domains, themes, and examples. A supplemental focus group of racial/ethnic minority parents enhanced the sample's diversity and validated findings from the Parent Crowd. Results: Similar domains and themes emerged from responses of crowdsourcing and focus group participants. In each domain, parenting YC-T1D was challenging, but there was also substantial evidence of positive coping strategies and adaptability. Conclusions: The study yielded rich data to inform user-centered design of an Internet resource for parents of YC-T1D.